Multilevel series–parallel continuously regulated chopper applied flying capacitor topology. Issue 9 (8th July 2019) - Mori, Takao; Uezono, Keiichi; Funato, Hirohito; Haruna, Junnosuke
Abstract: This paper proposes a new configuration of the series–parallel continuously regulated chopper applying three‐level operation realized by flying capacitor topology. In the conventional two‐level operation, the increase in switching loss and volume of the inductor is problematic. In three‐level operations, both switching frequency and inductance of interconnecting inductor become half of those of two‐level operation under the condition of same current ripple and same ripple frequency. Using a low‐voltage power device, the switching loss can be reduced without increasing the volume of the inductor. The effectiveness of the proposed circuit was verified from steady‐state waveforms obtained by simulations. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.